Sociological study of the digital culture of a university teacher (using the example of the Moscow State Linguistic University) - V. A. Lapshov (Цифровая социология)
In the article, based on the study conducted by the sociological laboratory of the Moscow State Linguistic University (hereinafter referred to as MSLU), the essence and level of digital culture of a university teacher are determined, problematic areas of digitalisation of the educational process are identified, which require urgent measures to improve the current situation in the higher education system of the Russian Federation. The study has proved that the digital culture of the university teacher is their digital social competence formed in the course of professional activity as well as the driving force that determines the attitude towards the digitalisation of the educational process. The development level of the digital culture of a teacher at a linguistic university is below average. The majority of respondents have digital skills and use basic digital technologies in the learning process. The level of proficiency among teachers of the MSLU is comparable to the level of development of these skills among teachers at other Russian universities. At the same time, in terms of the level of competence in developing online courses and using their materials as additional educational material, teachers of the MSLU lag behind the all-Russian indicators. The main problematic areas of the digitalisation of the educational process are: low degree of equipment of audiences with modern technical means; low quality and availability of Internet communications on the territory of educational buildings; insufficient opportunities to improve the level of the digital culture of teaching staff in the field of modern digital technologies, etc.